Padronização de Elisa indireto para diagnóstico da leucose enzoótica bovina - Cláudia Fideles Resende (2017)
Enzootic bovine leukosis (EBL) is a natural infectious bovine disease caused by bovine leukemia virus (BLV). This disease has a worldwide distribution and the serological prevalence is high in the Brazilian cattle herds, with an important economic impact. The identification and isolation of positive animals are necessary to control the spread of the virus and serological tests have been used for this purpose. Agar gel Immunodifusion (AGID) was considered for many years the test of choice. However, immunoenzymatic assays (ELISA) have been developed and, when compared to the AGID, have higher sensitivity, faster and more objective reading, and also allow the processing of a large number of samples simultaneously. The importing of ELISA kits from other countries is an expensive and time consuming process. Because of this, the most used diagnostic tool in Brazil is still the AGID. Thus, the objective of this study was to standardize an indirect ELISA (iELISA) for diagnosis of EBL. The BLV-infected and BVDV-free Tb1Lu cell line was used for antigen production. Seventy-three serum samples from calves collected before and after colostrum feeding were classified as negative or positive by AGID (reference). For iELISA standardization, different antigen concentrations, positive and negative control sera and conjugates dilutions were evaluated. Subsequently, the results were compared with those obtained by the AGID and by the Chekit Leucose-Serum commercial ELISA (IDEXX Laboratories, USA). The final protocol for the iELISA was defined under the following conditions: 1.0g of crude antigen per well, serum test at 1:25 dilution and conjugate diluted 1: 5000. The sensitivity and specificity related to the AGID were 94.44% and 75.68%, respectively, and PPV = 79.1% and NPV = 93.3%. The agreement between the tests was 84% and the Kappa index was 0.699. The iELISA showed sensitivity of 92.6% and specificity of 87.09% in comparison to Chekit ELISA. The concordance between the tests was 90.27% and the Kappa index 0.801. Nine samples were negative for AGID and positive for iELISA. When compared to the Chekit ELISA, the iELISA showed higher sensitivity once classified as positive one sample with undetermined result in the commercial test, demonstrating that the assay developed can be used alternatively to the Chekit ELISA. The iELISA developed in this work is, therefore, a diagnostic tool complementary to the AGID for the control of EBL in Brazil.